On some properties of Gelfond – Leontiev generalized integration operators - Linchuk, N. E.; Linchuk, S. S. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
In a class of linear continuous operators acting in spaces of functions analytic in domains, we describe in various forms isomorphisms which commute with a degree of the Gelfond – Leontiev generalized integration. We also obtain images of all closed subspaces of a space of analytic functions which are invariant with respect to the degree of the Gelfond – Leontiev generalized integration.